La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.

The emergence of a new reality for Quebec Women Composers - Lefebvre, Marie-Thérèse (With a Song in Her Heart: A Celebration of Canadian Women Composers, 1995)

Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Whose Playground, Which Games and What Rules?: Women Composers in the Digital Playground - McCartney, Andra (International Composer Music Association, 1995)
Keywords: Pas de lien web

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les Bâtisseuses de la Cité, 1993)

Les femmes dans l'industrie du disque et du spectacle au Québec depuis 1945 - Tremblay, Danielle (En avant la chanson!, 1993)
Recueil de textes sur différentes facettes de la chanson populaire au Québec et au Canada. Comprend un large éventail de pistes de recherche : une esquisse de l'historiographie de la chanson québécoise; un aperçu des fabricants de disques au Québec; la place des femmes dans l'industrie du disque et du spectacle; le statut social des artistes; ou encore, la figure emblématique que constitue Robert Paquette chez les Ontariens.

Marie-Claire Séguin - Kivi, K. Linda (Canadian Women Making Music, 1992)